Mitigation of Aerodynamic Uplift Loads Using Roof Integrated Wind Turbine Systems - Gan Chowdhury, Arindam; Moravej, Mohammadtaghi; Zisis, Ioannis; Irwin, Peter; Tremante, Andres; Hajra, Bodhisatta (Frontiers in Built Environment, 2019)
Coastal areas of the US are affected by extreme wind events, including hurricanes. Roofs are the most vulnerable building components as they are often damaged by high wind uplift forces acting on the edges and corners. This study investigates the application of a mitigation strategy, in the form of an Aerodynamics Mitigation and Power System (AMPS) (US Patent, Gan Chowdhury et al., Patent Number: US 9,951,752 B2, April 2018), designed to simultaneously reduce wind damage and provide power to buildings. The system consists of horizontal axis wind turbines, integrated to roof edges with or without gutters. Four sets of testing on a flat roof low rise building model (without gutters) -- including a bare deck configuration (i.e. without AMPS) and three cases where the roof corner was fitted with AMPS -- were conducted at the Wall of Wind Experimental Facility at Florida International University. In one of the configurations, the wind turbines were placed slightly above the roof edge, while in the other two configurations, the turbines were placed closer to the roof edge. Wind directions tested ranged from 0º to 90º (considering roof geometric symmetry). Estimation of area-averaged mean and peak pressure coefficients were made for various locations on the roof for the three different configurations, and compared with the case of no mitigation. Results show that for wind directions tested, significant reduction in mean and peak pressure coefficients (reduced suction) were obtained in those cases where the wind turbines were placed closer to the roof edge as compared to the bare roof deck case. Flow visualization studies showed that the turbines helped to disrupt the conical vortices caused by cornering winds, thereby reducing the wind uplift forces on the roof. This study shows that the AMPS can be utilized to prevent wind-induced damage to the roof. Future research will include estimation of the: (1) potential wind energy production using the mitigation system under various wind conditions, (ii) effectiveness of AMPS in mitigating wind loading on other kinds of buildings (e.g., gable and hip roof buildings), and (iii) load transferred from the system to the roof.